تحضير ودراسة خصائص مادة مركبة ذات مصفوفة من البولي استر غير المشبع مقواة بألياف نبات الديس - قوادري, زينات (Université de m'sila, 2014)
The purpose and aim of this study is the exploitation of some types of fibers wich exist in southeast of m’sila which is diss fiber (ampelodesma muritanica) because it possesses and characterizes a high physical and mechanical properties We performed the extraction which identifies the essential component of diss fiber( cellulose, hemicelluloses and lignine) ,in addition to this we studied the effect of chemical treatment on the properties of fiber (soud effect) In the last, we prepared the composite by graft the polymeric matrix (unsaturated polyester: as adhesive) by treated and untreated fiber (diss: as strengthening and reinforcing material) Among the tests used in order to identify the extent of the effect of chemical treatment , we recall test FTIR, DRX, microscopic, traction and flexion test.
Keywords: : Diss, Cellulose, extraction , alkali treatment ,polyester ,composite